2002
DOI: 10.1046/j.1365-2842.2002.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abutment substrate and ceramic thickness on the colour of heat‐pressed ceramic crowns

Abstract: All-ceramic crowns made of leucite-based heat-pressed ceramics are widely used to restore non-vital teeth in conjunction with various post and core materials. However, as some light passes through the ceramic, the colour of the abutment substrate can negatively affect the final aesthetic appearance of the all-ceramic crown. In this study, we made background specimens simulating gold-alloy cast posts and other simulating porcelain veneered cast posts, overlaid different thickness of heat-pressed ceramic on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 7 publications
4
56
0
8
Order By: Relevance
“…Ceramics are also selected for restorations due to their excellent biocompatibility 3) and satisfactory mechanical properties 4,5) . In order to reproduce the correct natural appearance of dental restorations, it is necessary to understand some important optical phenomena like reflectance, transmittance, absorption and fluorescence [7][8][9][10][11][12] . Transmittance is particularly important for dental restorations and is also referred to as the amount of light transmitted through the material after disregarding the reflected and absorbed light 13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramics are also selected for restorations due to their excellent biocompatibility 3) and satisfactory mechanical properties 4,5) . In order to reproduce the correct natural appearance of dental restorations, it is necessary to understand some important optical phenomena like reflectance, transmittance, absorption and fluorescence [7][8][9][10][11][12] . Transmittance is particularly important for dental restorations and is also referred to as the amount of light transmitted through the material after disregarding the reflected and absorbed light 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the tooth substrate shade Impact of background on color, transmittance, and fluorescence of leucite based ceramics has great impact on the final esthetic result of all ceramicrestorations 10) and could be one of the most important factors affecting their appearance 11,12) . Ceramic veneers are usually fabricated as thin layers, especially when preservation of dental structures is desired by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…15,32 Core ceramics with high opacity are often used to mask the discolored substrates using the least amount of restoration thickness. 16,30,33 Accurate and reliable color assessment is a prerequisite for successful esthetic outcome. While subjective and qualitative methods, i.e., shade guides and photographic methods lead to unpredictable results, electronic intraoral devices such as colorimeters and spectrophometers can objectively detect color differences.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Dozic et al (2003) was able to demonstrate that a 0.70mm ceramic core has the capability to mask a discoloring background under their layered specimens, which would otherwise display an increased ΔE. The combined works of Chaiyabutr et al (2011);Volpato et al (2009), andNakamura et al (2002) indicate that ceramic thicknesses 1.5mm and greater are capable of masking dark substrates that would inherently lead to larger ΔE values.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have been conducted on how thickness can affect the optical properties of all-ceramic systems (Begum et al, 2014;Chaiyabutr et al, 2011;de Azevedo Cubas et al, 2011;Dozic et al, 2003;W. Kang et al, 2018;Kurklu et al, 2013;Nakamura, Saito, Fuyikawa, & Ishigaki, 2002;Niu et al, 2014;O. Ozturk et al, 2008;Pires, Novais, Araujo, & Pegoraro, 2017;Sari et al, 2017;Sen & Us, 2017;Silva et al, 2012;Vichi et al, 2011;Volpato, Monteiro, de Andrada, Fredel, & Petter, 2009;Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%